Acute Kidney Injury in Patients With Acute Chemical Poisoning: the Experience of the Toxicological Center in Ryazan - N. V. Shatrova; M. N. Rudakova; L. G. Zaytseva; Zh. A. Varenova (Неотложная медицинская помощь, 2021)
Relevance. Acute kidney injury (AKI) is one of the leading causes of death worldwide. However, the epidemiology of AKI is not well understood. In Russia, toxic kidney damage plays a significant role in the nosological structure of AKI — 12.2%.Aim of study. To study the features of AKI in patients with acute chemical poisoning.Material and methods. We analyzed 26 case histories of patients with acute chemical poisoning with AKI (according to KDIGO). The comparison group included 25 patients with acute chemical poisoning without AKI. All patients were hospitalized in a toxicological center on the basis of the emergency department of the Ryazan Region State Budgetary Institution “City Clinical Emergency Hospital” (SBI RR “CCH EMC”) in 2016–2018. The analysis of the annual reports of the chief toxicologist of the Ministry of Health of the Ryazan Region for 2016–2018 was carried out. Data processing was performed using Microsoft Office Excel 2013 and on the website medstatistic.ru (Pearson’s chi-square test and Fisher’s exact test).Results. In most patients AKI developed during poisoning with cauterizing action substances - 38.4% (23% - vinegar essence, 15.4% - unidentified cauterizing action substance). The poisoning with alcohol substitutes (12%) took the 2nd place, with narcotic substances (8%) – the 3 rd place. Also, isolated cases of AKI (4% each) were reported in case of poisoning with pregabalin, tramadol, ketorol and ethanol. Poisoning with an unknown toxicant was noted in 29.6% of cases. Most patients (69.2%.) had stage 3 AKI. The second stage was registered in 7.7% of patients, the first — in 23.1%. Proteinuria was detected in all patients who underwent common urine test (CUT). Infusion therapy using crystalloids was performed in 100% of cases.Conclusion. Acute renal injury most often develops in acute poisoning with cauterizing poisons. The development of acute kidney injury in acute chemical poisoning leads to an increased risk of death. Acute kidney injury is the second most common immediate cause of death in acute chemical poisoning. Infusion therapy is an integral part of the management of toxicological patients with acute kidney injury.